Conversion of tropical forests to water buffalo pastures in lower Amazonia: Carbon losses and social carbon costs - J. Boone Kauffman; Fernanda M. Souza; Rodolfo F. Costa; Antonio Elves Barreto da Silva; Tiago O. Ferreira; J. Patrick Megonigal; Rasis Ritonga; Adi Gangga; Nisa Novita; Carla F. O. Pacheco; Angelo Fraga Bernardino (Ecosphere)
Abstract Tropical peat swamp forests provide many important ecosystem services, especially their function as global carbon sinks. These carbon‐rich wetlands are widespread in South America, yet few studies have examined carbon stocks or losses due to land use change. In the lower Amazon, they are being converted to pastures largely utilized by domestic water buffalo (Bubalus bubalis). We quantified carbon stocks in intact peat forests and recently converted pastures (<10 years) at the Lago Piratuba Biosphere Reserve (LPBR) in the lower Amazon of Brazil. The soils of intact forests were typified by shallow organic (peat) horizons at the soil surface. The mean total ecosystem carbon stock (TECS) in intact forests was 354 ± 28 Mg C ha−1. In contrast, the TECS of disturbed sites was significantly lower (p = 0.02) with a mean of 248 ± 17 Mg C ha−1. We estimated greenhouse gas (GHG) emissions from water buffalo (due to enteric fermentation and manure deposition) to be 7.5 Mg CO2e ha−1 year−1. Considering GHG emissions from this land use, the social carbon costs (SCCs) arising from the degradation of coastal Amazon peatlands are as high as US$2742 ha−1 year−1. The SCC of meat produced from this land use is as high as US$100/kg of meat produced, which far exceeds the economic returns from livestock. Based on the estimated numbers of water buffalo for the southern portion of the LPBR and the time since initial disturbance, the annual GHG emissions from this land use are estimated to be 602,846 Mg CO2e year−1 with an SCC as high as US$111,526,524 million year−1. This land use also eliminates opportunity values and services of carbon storage and biodiversity that would be possible from a regenerating biosphere reserve.